On the Typology of Social Utopia - Gudonis, Kazimieras (Problemos, 1980)
A variety of forms of social utopia, which is a recurrent conception in the history of social theories, requires a typological characteristics. The author of the present paper attempts to base the typology of social utopia on a number of relevant features, viz.: the setting of an utopian conception in terms of time and place, its ethic and political evaluation, the Weltanschauung propagated by the authors of a utopia and the effects of a social utopia on progressive social development.